A modern conceptual framework for study and treatment of Meniere’s disease - Chari, Divya A.; Bose, Arpan; Ramirez, Kimberly; Robles-Bolivar, Paula; Lin, Kuei-You; Juliano, Amy F.; Rauch, Steven D.; Eckhard, Andreas H. (Frontiers in Neurology, 2025)
Prosper Meniere made his immortal contribution to the field of otology in 1861. At that time, all manner of “fits” were lumped together under the diagnosis of “apoplectiform cerebral congestion”—too much blood in the brain. His genius was to identify a specific subset of this heterogeneous pool whose cardinal symptoms, tinnitus, fluctuating progressive deafness, and episodic vertigo, were due to dysfunction of the inner ear. Seventy-seven years later, in 1938, Hallpike and Cairns in England and Yamakawa in Japan identified cochleosaccular endolymphatic hydrops (EH) as the histopathologic correlate of Meniere’s disease (MD). Over the 85 years since then, many theories to explain the symptoms of MD have come and gone. A consensus has slowly emerged that patients with this condition have a failure of inner ear homeostasis. The cause(s) of this homeostatic failure and the mechanism(s) by which this failure leads to fluctuating progressive sensorineural hearing loss and episodic vertigo has remained elusive. In the last few years, new techniques and findings in temporal bone histopathology and in vivo temporal bone imaging have yielded breakthroughs in this field. We are now recapitulating Meniere’s approach by taking the heterogeneous population of patients with MD and segregating them into specific subtypes based upon clinical phenotype. Salient clinical features include vestibular aqueduct and endolymphatic sac morphology, age at symptom onset, sex, and incidence of bilateral involvement. Furthermore, new imaging modalities enable unequivocal diagnosis of EH, transitioning MD from a “clinical” diagnosis to one based upon specific objective criteria. These breakthroughs have opened the door to genetic analyses, consideration of comorbid clinical disorders, especially migraine, and potential new treatments, and demand that we revisit all the various treatments that have been considered previously. They also demand new and more stringent criteria for any publication about this condition. In this paper we will review these new findings, discuss their immediate implications for clinical practice, and consider some of the most pressing research questions for near- and long-term address.